Specifying a manufacturing knowledge reuse framework - Baxter, David; Roy, Rajkumar; Gao, Xiaoyu (Taylor and Francis, 2007)
This paper presents the first part of a design life cycle knowledge reuse framework: manufacturing knowledge reuse for design. The results of a manufacturing knowledge capture and classification exercise are presented. The research methodology applies the critical incident technique for the interviews. Interview notes were analysed using qualitative content analysis, identifying themes through coding. The interview content from which themes are identified are then analysed to identify the knowledge content. Both the themes and the knowledge content are cross referenced to any identify differences according to knowledge applied by role. A knowledge structure and ontology framework is proposed to support the storage and reuse of knowledge relating to manufacturing in the design process.